2015
DOI: 10.5194/bg-12-6999-2015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of forest harvesting on water quality and fluorescence characteristics of dissolved organic matter in eastern Canadian Boreal Shield lakes in summer

Abstract: Abstract. Forestry activities in the Canadian Boreal region have increased in the last decades, raising concerns about their potential impact on aquatic ecosystems. Water quality and fluorescence characteristics of dissolved organic matter (DOM) were measured over a 3-year period in eight eastern Boreal Shield lakes: four lakes were studied before, 1 and 2 years after forest harvesting (perturbed lakes) and compared with four undisturbed reference lakes (unperturbed lakes) sampled at the same time. ANOVAs show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Numerous studies have confirmed that soil erosion in skid trails was at its highest rate in the first years after machine traffic events and then decreased significantly, primarily due to vegetation regrowth [8,44,45]. For example, Boggs et al [46] studied the effect of forest harvesting on water quantity and quality in North Carolina, USA, and showed that the amount of sediment as well as the amount of nitrate in the water reached its maximum value two years after harvesting, and then its value decreased, probably as a consequence of the regrowth of tree and understory vegetation. Also, in Canada, Glaz et al [47] investigated the effect of forest harvesting on the water quality of lakes near harvested forests, and showed a significant difference in the amount of phosphorus in the control and logged samples one year after disturbance.…”
Section: Introductionmentioning
confidence: 95%
“…Numerous studies have confirmed that soil erosion in skid trails was at its highest rate in the first years after machine traffic events and then decreased significantly, primarily due to vegetation regrowth [8,44,45]. For example, Boggs et al [46] studied the effect of forest harvesting on water quantity and quality in North Carolina, USA, and showed that the amount of sediment as well as the amount of nitrate in the water reached its maximum value two years after harvesting, and then its value decreased, probably as a consequence of the regrowth of tree and understory vegetation. Also, in Canada, Glaz et al [47] investigated the effect of forest harvesting on the water quality of lakes near harvested forests, and showed a significant difference in the amount of phosphorus in the control and logged samples one year after disturbance.…”
Section: Introductionmentioning
confidence: 95%
“…Increasing DOC concentrations derived from terrestrial sources can themselves potentially increase Hg bioaccumulation in estuarine ecosystem food webs (French et al, 2014;Jonsson et al, 2014;Jonsson et al, 2017). This is also relevant in boreal ecosystems as common forest harvest activities can enhance terrestrial OM input to lake (Meunier et al, 2016), resulting in increased DOC concentrations (O'Driscoll et al, 2006;Glaz et al, 2015), and sometimes higher Hg and/or MeHg input from terrestrial to aquatic ecosystems (Eklöf et al, 2013;Kronberg et al, 2016). This can increase Hg bioaccumulation in food webs (Bishop et al, 2009;Hongve et al, 2012;Wu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%